3x-3+8x-6=8x+3x-12

Simple and best practice solution for 3x-3+8x-6=8x+3x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3+8x-6=8x+3x-12 equation:


Simplifying
3x + -3 + 8x + -6 = 8x + 3x + -12

Reorder the terms:
-3 + -6 + 3x + 8x = 8x + 3x + -12

Combine like terms: -3 + -6 = -9
-9 + 3x + 8x = 8x + 3x + -12

Combine like terms: 3x + 8x = 11x
-9 + 11x = 8x + 3x + -12

Reorder the terms:
-9 + 11x = -12 + 8x + 3x

Combine like terms: 8x + 3x = 11x
-9 + 11x = -12 + 11x

Add '-11x' to each side of the equation.
-9 + 11x + -11x = -12 + 11x + -11x

Combine like terms: 11x + -11x = 0
-9 + 0 = -12 + 11x + -11x
-9 = -12 + 11x + -11x

Combine like terms: 11x + -11x = 0
-9 = -12 + 0
-9 = -12

Solving
-9 = -12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6-7(a+1)=-3(2-a) | | 2(n+5)=-8 | | -3x+1x= | | -2=7x-2(x-4) | | -4b=6 | | 7x-(10+6x)-(8x+4)=0 | | 30r=18 | | -9(x+2)+10x= | | 4x+80=3x-5 | | 4x+900=x | | 2(x+3)-(4+5x)=16+4x | | -2x-8=20 | | bc=9x-4 | | y=-2x^2-1 | | 7-9x+6x= | | 5(w-8)-2=3(-4w+8)-3w | | 2xy+3y=7 | | 3(p-4)=16 | | -7(m-3)=35-m | | x-3x=7x | | 2y^4(7y^2-9y+4)= | | x-64=0 | | -(-x+9y+9)= | | 3+3(4*c)= | | 0.60x+0.20=400x(0.50) | | 4x+8=9x-11 | | (86x+80y)-(8x+37y)= | | 7x-x^2-12=0 | | -44-9z=31-3z | | 3705-120= | | 3x+4x+5x=72 | | x^3-x^2+2x=0 |

Equations solver categories